Novel Insight of CircRNAs in Cervical Cancer: Potential Biomarkers and Therapeutic Target - Wu, Maomao; Han, Yanxun; Gong, Xiangfei; Wan, Ke; Liu, Yuchen; Zhou, Yi; Zhang, Lizhi; Tang, Guozheng; Fang, Hui; Chen, Bangjie; Yang, Fan; Zhao, Qing; et al. (Frontiers in Medicine, 2022)
Cervical cancer (CC) is responsible for one of the major cancer incidence and mortality worldwide. Notably, many novel studies have found that multiple ncRNAs were implicated in the progression of CC. Circular RNAs (circRNAs), as a new star of ncRNAs, are characterized by a single-stranded covalently closed loop structure and play vital roles in maintaining the cell development and other physiological processes. The functions of these dysregulated circRNAs appear to be context specific, with evidence of having a dual role in both oncogenes and tumor suppression depending on the cellular environment in which they are expressed. For example, Cdr1as exerts anti-oncogenic functions by sponging microRNA-135a in bladder cancer nevertheless acting as an oncogene in HCC partly through targeting miR-7. Emerging evidence reveals the essential function roles of circRNAs in the occurrence and development of human diseases. Among those, circRNAs are aberrantly expressed in CC and are involved in the progression of CC. Therefore, the unique expression profiles of circRNAs were related to the diagnosis, prognosis, and therapeutic outcome in CC. In this review, we focused on several circRNAs specific to CC, and assess their functions to uncover the molecular mechanisms of tumor initiation and progression in CC. Taken together, these data promised that circRNAs may be utilized as early detection biomarkers and potential therapeutic targets in CC patients.